Penerapan Database Impor dan Ekspor Menggunakan SQL Server 2008 - Yuda Mahendra Hasibuan; Muhammad Irwan Padli Nasution (MAMEN: Jurnal Manajemen, 2023)
Import data is the process of retrieving data from another database, such as Microsoft Access to SQL Server 2008, can also be Microsoft Excel, you have imported data into SQL Server 2008. We can import from Microsoft Access if we wish, all tables and data or only some of them will be imported from Microsoft Excel. If we import from Microsoft Access, then yes the primary key is lost and the datatype is changed according to the existing data type in SQL Server 2008 and imported from Microsoft Excel. The data export process is the process of moving data from a database in SQL Server 2008, to another database, such as Microsoft Access, or it could also be Microsoft Excel. We can export data from SQL Server 2008 to Microsoft Access all tables and data or just some of them so if we do this export to Microsoft Excel. This article covers how to export and import data the program uses SQL Server 2008. The first step taken is a case study of the Microsoft Access Teaching Schedule database which is made of a link along with the information content. Next, how to import the database to SQL Server 2008, create primary keys and relations to form DBMS graphs with SQL Server 2008. Based on the database that was created, we export the chart to Microsoft Excel.